Spirulina and chlorella derived hard candies as functional food - Shafia Maryam; Mecit Halil Oztop; Sarper Doğdu; Mehmet Ali Marangoz; Zeshan Zeshan; M. Qasim Hayat; Ramish Riaz; Muhammad Waqas Alam Chattha; Hussnain Ahmed Janjua (Journal of Functional Foods)
Hard candies with spirulina (Arthrospira platensis) and chlorella (Chlorella vulgaris) biomass were prepared. Their characterization include pH, moisture, hardness, color, total soluble solids, antioxidant, phenols, and flavonoid content. Safety tests were conducted on rats to examine protective effects of these candies against arsenate poisoning. Algal hard candies were slightly acidic, had low moisture content, and achieved optimal hardness. These candies contain 0.4 GAE mg/g phenols and 0.5 CAE mg/g flavonoids. Upon in-vivo analysis, algae candies increased acetyl cholinesterase, malondialdehyde, catalase, superoxide dismutase, and glutathione concentration in blood serum. Histopathology analysis revealed significant restoration in the liver, kidneys, and brain of Wistar rats treated with algal candies following arsenate poisoning. The phenolic and flavonoid content along with activation of antioxidative enzymes reveals radical scavenging activity of hard candies. Spirulina and chlorella candies may boost immune system, improving gut health, and enhancing antioxidant defense mechanisms and can be used as functional food.